2020
DOI: 10.3389/fonc.2020.00459
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prediction of Extramural Venous Invasion in Rectal Cancer: Comparison of the Diagnostic Efficacy of Radiomics Models and Quantitative Dynamic Contrast-Enhanced Magnetic Resonance Imaging

Abstract: Background: To compare the diagnostic performance of radiomics models with that of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) perfusion parameters for the preoperative prediction of extramural venous invasion (EMVI) in rectal cancer patients and to develop a preoperative nomogram for predicting the EMVI status.Methods: In total, 106 rectal cancer patients were enrolled in our study. All patients under went preoperative rectal high-resolution MRI and DCE-MRI. We built five models based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 40 publications
(54 reference statements)
1
27
1
Order By: Relevance
“…Compared to the same type of research by Yu et al. ( 20 ), the diagnostic efficiency of the nomogram in the training set was lower than that of the radiomics nomogram constructed in their study (AUC = 0.904), while the diagnostic efficiency of the nomogram in the test set was higher than that of theirs (AUC = 0.812), which indicated better stability of our nomogram. This may be caused by the different radiomics signature.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Compared to the same type of research by Yu et al. ( 20 ), the diagnostic efficiency of the nomogram in the training set was lower than that of the radiomics nomogram constructed in their study (AUC = 0.904), while the diagnostic efficiency of the nomogram in the test set was higher than that of theirs (AUC = 0.812), which indicated better stability of our nomogram. This may be caused by the different radiomics signature.…”
Section: Discussioncontrasting
confidence: 79%
“…However, to our knowledge, only Yu et al. have focused on predicting EMVI based on radiomics ( 20 ). But their results showed that their radiomics model had poor stability and low sensitivity, which may be resulted from their small amount of data and defects in the modeling method.…”
Section: Introductionmentioning
confidence: 99%
“…There is a trend of increasing interest in radiomics features as non-invasive imaging tools for estimation of pathological or histological features, distinction of benign and malignant entities, prediction of prognosis or treatment response, and inference to the genetic expression ( 10 13 ). These imaging biomarkers possess a potential to be more cost effective and provide a more individualized medical care ( 11 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics shows multiple advantages in evaluating therapeutic response over traditional imaging analysis [7][8][9][10], thereby providing important details of tissue features [11][12][13][14][15][16][17][18][19]. Mounting evidence indicates potential benefits for radiomics in assessing therapeutic response in LARC [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%